Detection by gas chromatography of 3-deoxy-D-manno-2-octulosonic acid and L-glycero-D-manno-heptose in whole cells of Neisseria elongata. - Guerrant, G O (1986)
Lipopolysaccharide components 3-deoxy-D-manno-2-octulosonic acid and L-glycero-D-manno-heptose were detected in hydrolysates from whole cells of Neisseria elongata by gas-liquid chromatography. Cells from a single plate were hydrolyzed, and carbohydrate components were converted to aldononitrile and O-methyloxime acetate derivatives for subsequent analyses by gas-liquid chromatography. 3-Deoxy-D-manno-2-octulosonic acid was well separated from other cell components as the O-methyloxime acetate derivative. With both derivatives, L-glycero-D-manno-heptose was readily identified by their different retention times. The procedure requires only a relatively small number of cells, and detection is accomplished without prior isolation of the lipopolysaccharide.